Faecal Contamination in Ground Water Resources of Urban Areas of Ujjain (International Journal of Scientific Research and Management (IJSRM), 2020)
Ground water is one of the most important natural resource next to air being essential for life. Quality of ground water depends upon natural process, such as wet/dry condition, salts, many geogenic and anthropogenic activities. Among all contamination ground water is more susceptible to microbial contamination. According to WHO report about 80% of all diseases in human being are caused due to drinking water contaminated by bacteria of faecal origin. Various water born diseases are prevalent in Ujjain like typhoid, dysentery, jaundice, amebeosis, colitis etc. Purpose of the study was to assess the bacterial contamination of faecal origin in ground water resources of urban area of Ujjain. For this ground water samples (well, bore well and hand pump) were collected from 6 sub areas of Ujjain city. For the assessment of bacterial contamination of faecal origin H2S strip test of Manja,et.al.(1982) was used. Results clearly indicated that bore well water was found to be safe for drinking, domestic and other purposes.